The challenges of facilities management for pondok institution in Malaysia / Muhammad Shahrol Hafiz Ibrahim, Yuhainis Abdul Talib and Nor Aini Salleh - Hafiz Ibrahim, Muhammad Shahrol (2022)
The pondok educational system is the earliest in the Malay Archipelago that focused on Islamic studies. Most pondok institutions in Malaysia depend on waqaf educational institutions. Since then, the development of the pondok required more attention in many aspects. There are limited studies on the issues due to lack of awareness on the need of strategic facilities management (FM) in order to avoid buildings being dilapidated and deteriorated. The aim of this paper is to identify the challenges of managing the pondok facilities. Content analysis was used in this paper by critically reviewing previous literature. Finding shows these three challenges are widely discussed in the articles among six challenges found. They are; (i) lack in fund allocation (ii) building age (iii) lack in expertise and staff. Thus, it can be concluded that the development of pondok institutions required sufficient financial support by the authority in order to ensure the sustainability of these institutions.